PENGARUH DEBT TO EQUITY RATIO, RETURN ON EQUITY DAN TOTAL ASSET TURNOVER TERHADAP NILAI PERUSAHAAN PADA PT ADHI KARYA (PERSERO) TBK PERIODE 2012-2022 - Rahmadani Putra, Yopie; Jati, Waluyo (Journal of Research and Publication Innovation, 2024)
This research aims to determine the effect of Debt to Equity Ratio, Return On Equity and Total Asset Turnover on Company Value at PT Adhi Karya (Persero) Tbk for the period 2012 to 2022. The population of this research is the financial statements of PT Adhi Karya (Persero) Tbk. The sample used in this research is the balance sheet and profit and loss report for the 2012-2022 period. The research method used is an associative quantitative approach. The data analysis techniques used are descriptive statistical analysis, classical assumption test, correlation coefficient test, coefficient of determination test, simple and multiple linear regression analysis and hypothesis testing, namely the t test and F test. The results of the research show that DER has no effect on company value, this is shown by the value of 0.667 < 1.894 with a significant value of 0.526 > 0.05. ROE has no effect on Company Value, this is shown by the value -1.062 < 1.894 with a significant value of 0.324 > 0.050. TATO has an effect on Company Value, this is shown by the value of 2.387 > 1.894 with a significant value of 0.048 < 0.050. The variables DER, ROE, TATO simultaneously do not contribute to Company Value, this is indicated by the value of 4.14 < 4.35 with a significance value of 0.055 > 0.050. The Determination Value of 0.640 indicates that DER, ROE, and TATO simultaneously contribute to Company Value of 64.0%, while the remaining 36.0% is influenced by other variables.